Predictors of Prediabetes and Undiagnosed Diabetes Mellitus Based on HbA1c Levels in Indonesia - Irma Surya Kusuma; Syahrizal Syarif (Faculty of Public Health, Sriwijaya University, 2023)
Prediabetes and Undiagnosed Diabetes Mellitus (UDDM) are associated with an increased risk of diabetes complications and other cardiovascular diseases. Early detection of both health problems is expected to reduce the burden of non-communicable diseases in the future. The purpose of this study is to investigate predictors of prediabetes and UDDM based on HbA1c levels among population ≥ 15 years old in Indonesia. This cross-sectional study involved 6,065 respondents of Indonesian Family Life Survey 5 (IFLS 5) who met the inclusion and exclusion criteria. Data associated with sociodemographic characteristics, lifestyle risk factors, hypertension, and obesity were obtained. Prediabetes was defined as HbA1c between 5.7-6.4%, while diabetes was defined as HbA1c ≥ 6.5%. Multinomial logistic regression analysis was performed to estimate adjusted Odds Ratio (aOR). The results showed that predictors of prediabetes were age, gender, marital status, and obesity, while predictors of UDDM were age, hypertension, and obesity. Identification of risk factors and early detection of prediabetes and UDDM is important, so that appropriate intervention can be given immediately to prevent complications.